Can serum amyloid A or macrophage colony stimulating factor serve as marker of amyloid formation process? - Rysavá, R; Merta, M; Tesar, V; Jirsa, M; Zima, T (Biochemistry and molecular biology international, 1999)
Amyloid formation depends on amyloid precursor production and is influenced by the activity of the underlying disorder and mediated by some proinflammatory cytokines. In this pilot study we tried to find some specific markers that could establish the activity of the disease. We investigated 45 samples of sera and 38 samples of urine from patients (pts) with secondary amyloidosis (AA), primary amyloidosis (AL), systemic autoimmune diseases with renal impairment (Vasc) and healthy controls (Co). Pts with AA had increased plasma levels of TNF alpha (9.97 +/- 4.22 vs. 2.63 +/- 1.34 pg/mL, p < 0.001) and SAA (43.14 +/- 16.0 vs. 3.42 +/- 0.7 ng/mL, p < 0.05) in comparison with Co. Plasma levels of M-CSF in the AA group were significantly increased in comparison with Co (1077.34 +/- 238.6 vs. 137.71 +/- 19.6, pg/mL, p < 0.001) and also in comparison with Vasc (482.24 +/- 86.7 pg/mL, p < 0.05). Urinary excretions of TNF alpha (8.92 +/- 8.1 vs. 0.17 +/- 0.11 microgram/mol creatinine, p < 0.01), sIL-6R (1.39 +/- 1.14 vs. 0.07 +/- 0.05 g/mol creatinine, p < 0.01) and M-CSF (650.2 +/- 153.7 vs. 33.3 +/- 8.6 micrograms/mol creatinine, p < 0.01) in AA were significantly increased in comparison with Co. Pts with AL had increased plasma levels of M-CSF (819.83 +/- 264.2 vs. 137.71 +/- 19.6 pg/mL, p < 0.05) and urinary excretion of M-CSF (865.0 +/- 188.4 vs. 33.3 +/- 8.6 micrograms/mol creatinine, p < 0.01) in comparison with Co. SAA has a low specificity for amyloidosis but is a sensitive acute phase reactant. TNF alpha, a proinflammatory cytokine, may reflect the activity of the underlying diseases in secondary amyloidosis. M-CSF was increased both in plasma and urine in amyloidosis groups and seems to be the most promising (possibly specific) marker of amyloidosis.
Keywords: Amyloidosis; autoimunitní nemoci; Humans; cytokiny; analýza rozptylu; ELISA; Analysis of Variance; lidé; Biomarkers; Enzyme-Linked Immunosorbent Assay; amyloid; Autoimmune Diseases; Amyloid; amyloidóza; faktor stimulující kolonie makrofágů; biologické markery; Macrophage Colony-Stimulating Factor; sérový amyloid A; Cytokines; Serum Amyloid A Protein